Asleep : the forgotten epidemic that remains one of medicine's greatest mysteries - Crosby, Molly Caldwell (New York : Berkley Books, 2011)
Crosby, acclaimed author of'The American Plague', explores the frightening history of a long forgotten disease--sleeping sickness--and details the frantic effort to conquer it before it strikes again.
An epidemic begins -- Constantin von Economo -- The London outbreak -- New York City -- Ruth -- The neurologist -- The medical investigators -- Adam -- Smith Ely Jelliffe -- The alienist -- Only the beginning -- Jessie -- 1925 -- A two-headed beast -- Madness -- Rosie -- The Neurological Institute -- The Matheson Commission -- Josephine B. Neal -- Vaccine trials -- Sylvia -- I have seen the future -- Philip -- Gray matter -- Past or prologue?
Includes bibliographical references and index.
Keywords: Epidemic encephalitis -- History; Encephalitis, Arbovirus -- epidemiology -- Europe -- Case Reports; Encephalitis, Arbovirus -- epidemiology -- United States -- Case Reports; Encephalitis, Arbovirus -- history -- Europe -- Case Reports; Encephalitis, Arbovirus -- history -- United States -- Case Reports; Disease Outbreaks -- history -- Europe -- Case Reports; Disease Outbreaks -- history -- United States -- Case Reports